Overview of Alginate: Its Antimicrobial Properties, Biocompatibility, Biodegradability and Range of Uses - Ankur Kumar; Ganesh Kumar Verma; Priyanka Singh; Avinash Bairwa; Priyanka Naithani; Jitender Gairolla; Ashish Kothari; Balram Ji Omar (Kurdish Studies, 2022)
Alginate is a polysaccharide that has been used extensively in the fields of biomedical and engineering, dentistry, pharmaceutical science, paper and textile industries, film formation, gelling, biocompatibility, biodegradability, readily available, medicine and antimicrobial properties. Its properties also include mucoadhesive properties, scaffolding, and welding roads. Alginates' hydrogels are essential for tissue engineering, wound healing, and controlled or sustained release medication delivery. We shall give a thorough introduction to Alginate and its uses in this review paper. As far as we are aware, no such useful information about alginate and its connection to drug susceptibility is available. Here, we paid additional attention to alginate's antimicrobial potential and how it relates to bacterial resistance.